Recurrent Hepatocellular Carcinoma in Patient with Crohn’s Disease: Incidental or Expected Outcome of Azathioprine? - Youssef Botros; Mary Mathews; Hiren Patel; Nihar Shah; Walid Baddoura; Andrew de la Torre (Case Reports in Gastrointestinal Medicine)
Hepatocellular carcinoma (HCC) usually occurs in patients with underlying risk factors such as liver cirrhosis and chronic hepatitis B. Although patients with Crohn’s disease (CD) are at an increased risk to develop malignancies such as colon cancer, the incidence of HCC in this population is extremely rare. We report a case of 62-year-old male with long history of CD treated with azathioprine (AZA) and aminosalicylic acid (ASA) who was incidentally diagnosed with HCC, for which left hepatectomy was done. Four years later during routine follow-up, patient had another hepatic lesion and underwent resection of the mass. The mechanism of occurrence of HCC in patient with CD is still controversial and may include immune mediated changes and medication related complications. AZA was reported in all case reports of CD that developed HCC. Through this report we hope to explore the complex pathophysiological mechanisms contributing to the development of HCC in the Crohn’s disease patient population.